Systemic tuberculosis with skin compromise in a pediatric patient with primary immunodeficiency - Cabrera-Enriquez , John A. (2024)
Background: Primary immunodeficiencies (PID) represent challenging pathologies in terms of diagnosis and treatment, with increased predisposition to recurrent respiratory and gastrointestinal infections. Case report: A paediatric patient with pathologic variants of genes IFNGR1 and TNFRSF13B, presented an atypical manifestation of tuberculosis, characterized by cutaneous lesions and lack of respiratory symptoms. Patient was initially treated for an atypical mycobacterial infection with partial favourable response. Following microbiological confirmation of Mycobacterium tuberculosis, a proper antibiotic regimen was initiated, resulting in complete recovery. Conclusion: PIDs increase the likelihood of atypical presentations of tuberculosis, complicating diagnosis and interfering with timely treatment. We report a case lacking the classic clinical criteria for immunodeficiency and with an atypical clinical presentation for M. tuberculosis infection, which led to a 2-month delay in the initiation of the most effective treatment.